The cytotoxic and cytocidal effect of colicin E3 on mammalian tissue cells - Smarda, J; Obdrzálek, V; Táborský, I; Mach, J (Folia microbiologica, 1978)
The plasma membrane of mammalian cells can mediate the cytotoxic and cytocidal effects of colicin E3. As little as 10(2) lethal units of purified colicin E3 per cell exert a pronounced cytocidal effect on human epithelial HeLa cells and as little as 10(4) lethal units per cell also on line L mouse fibroblasts in tissue culture. Cells in complete monolayers are rapidly killed, become spherical and shrink, they are detached from the support and finally autolyzed. The percentage of killed cells in both lines is directly proportional to the multiplicity of colicin used. The LD50 for HeLa cells is about 30 times lower than for L cells. At the multiplicity of 10(5) I.u., usually 100% HeLa and 90% L cells are killed in 2--3 days. Purified colicins E2 and D have no demonstrable cytological effect on HeLa cells, although DNA synthesis in L cells appears to be partly inhibited by colicin E2. The profound effect of colicin E3 on mammalian cells could be interpreted in a similar way as in bacteria, viz. as a specific cleavage of rRNA.
Keywords: HeLa buňky; buněčná adheze; L Cells; viabilita buněk; Cell Membrane; Cell Survival; koliciny; Cell Division; Colicins; HeLa Cells; buněčné dělení; L buňky (buněčná linie); Cell Adhesion; buněčná membrána